Designing a Collaboration Model Among Supply Chain Members to Reduce External Supply Risk in the Oil and Petrochemical Industry Using Game Theory - Agha Babaeipour, Parisa; Mohammadi, Mahmoud; Afshar Kazemi, Mohammad Ali (Management Strategies and Engineering Sciences, 2024)
The goal of supply chain management is to improve various activities of the components and levels of a supply chain to enhance the overall condition of the supply chain system. During this process, numerous conflicts and contradictions may arise between the objectives of different components and levels in achieving the overall goals of the supply chain. These disruptions and inconsistencies may gradually lead to a decline in the supply chain's strength and competitiveness. Conflicts may include issues related to pricing, inventory costs, and marketing disagreements. Given its characteristics, game theory is an appropriate tool to create collaboration within supply chains. In recent years, supply chain management has gained significant importance due to the globalization of business markets. A supply chain is a collection of facilities, suppliers, customers, products, and methods of inventory, supply, and distribution control. Supply chain management is the process of effectively planning, implementing, and controlling supply chain operations and is an effective method for maintaining a competitive advantage and improving organizational performance. The shorter product life cycle, the emergence of new technologies, and the expansion of supplier relationships and product development push the supply chain toward increased complexity. With rising complexity, the level of uncertainty and risk within the supply chain also increases. Supply chain risk is a potential event that disrupts the natural flow of materials and information in the chain, leading to disturbances. This article addresses the topic of designing a collaboration model among supply chain members to reduce external supply risk in the oil and petrochemical industry using game theory. Initially, by analyzing relevant data and outputs, the technical efficiency of domestic supplier companies was obtained using Data Envelopment Analysis (DEA) under the assumptions of constant and variable returns to scale. A statistical sample of 15 experts, with both academic and practical knowledge in financial management and experience in stock market operations, was selected for this purpose. Subsequently, game theory was utilized to design a collaboration model among supply chain members aimed at reducing external supply risk in the oil and petrochemical industry. The analysis focuses on selecting the best cooperative coalition and presenting a collaboration model based on the Shapley value. The findings indicate that this cooperative game model provides a structured approach for forming alliances among supply chain partners based on their contributions. By following the specified steps, companies can maximize their profits while enhancing supply chain collaboration.